Evaluation of the Government's Agroindustry MSME Based Community Empowerment Program - Meliaro Zalukhu; Sisman Prasetyo (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to evaluate the implementation of community empowerment policies based on agro-industry MSMEs (Micro, Small, and Medium Enterprises) implemented by the local government of North Nias Regency, with a case study in Afulu District. This research is a descriptive study adopting a qualitative approach. Data were collected through in-depth interviews, observation, and documentation. Research informants consisted of officials from the Department of Cooperatives and MSMEs of North Nias Regency, field extension officers, and agro-industry MSME actors. Data analysis was conducted descriptively using William N. Dunn’s policy evaluation criteria, which include effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings indicate that the implementation of agro-industry MSME empowerment policies in North Nias Regency has been carried out and shows a policy direction aligned with local agricultural and plantation potential. The program has encouraged the formation of agricultural product processing business groups and increased community awareness of the importance of adding value to agricultural products. However, the effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness of the program still face various constraints, particularly limited budgets, low intensity of field assistance, weak inter-agency synergy, and unequal community access to the program. These conditions hinder the achievement of program objectives to establish a sustainable agro-industry empowerment system, increase value-added agricultural products, and foster rural entrepreneurship. Therefore, improvements in policy implementation are needed through strengthening field mentoring quality, enhancing cross-sectoral coordination, and designing training programs that better match the needs of local agro-industry MSMEs.